Removal of dental surgical bur from maxillary sinus: a case report - Kim, Yeon Jung (2018)
The most commonly performed surgical procedure in Oral and Maxillofacial Surgery practices are the removal of impacted third molars. Extensive training, skill and experience allow this procedure to be performed in an atraumatic approach. The aim of this study was to drawing attention to the importance of the correct management of the complications cases of foreign body inside maxillary sinus after surgical removal of maxillary third molars. This is an unusual clinical case of a dental surgical bur accidentally displacement into the maxillary sinus during an upper third molar extraction surgery. After removal, the clinical case showed a satisfactory repair emphasizing the importance of a meticulous clinical examination to achieve a correct diagnosis and an appropriate treatment plan, which is essential for a favorable prognosis.